Which one comes ﬁrst, the tamarind or the Macrotermes termitarium? - Fandohan, Adandé Belarmain; ASSOGBADJO, ACHILLE EPHREM; SALAKO, Kolawolé Valère; Van Damme, Patrick; SINSIN, Brice (My University, 2012)
The relationship between termitaria and their vegetation is being increasingly studied. Nonetheless, our understanding of the order of establishment of termitaria and their associated vegetations which may be relevant for developing conservation plans is limited. This study focuses on order of establishment of Macrotermes termitaria and associated plant species with a special focus on Tamarindus indica and was to answer whether tamarind trees establish before termitaria or reversely? A comparative analysis of T. indica-dominated vegetations on termitaria and adjacent vegetations was undertaken using a matrix involving 80 relevés across four phytogeographical districts (phytodistricts), and an Indicator Species Analysis. We discussed how informative vegetation data could be on termitaria and tamarind trees establishment order. Whatever the phytodistrict, vegetations associated with termitaria were found to be much similar to those of their adjacent areas. Overall, only seven species (not including T. indica) out of a total of 63 recorded were found to be confined to termitaria. These results would suggest termitaria to not be a factor controlling establishment of T. indica and most of the species their host. Comparative vegetation analysis was thus found not to be enough to stand on termitaria and T. indica establishment order. However, termitaria-tamarind associations may be profitable to both tamarind trees and termites: termitaria may help mitigate drought on tamarind trees under increasing drought conditions while tamarind trees may offer food to termites. Integration of information on termite species’ feeding preferences and ecology was proposed in order to improve current state of knowledge on tamarind-termite relationship.
Keywords: plants-insect relationship; termitaria; indicator species; phytogeograpical districts